Strategi Calon Guru PAI Dalam Meningkatkan Kecintaan Alam Pada Generasi Mendatang - Divandra Rahmat Kurniawan; Marsha Nur Faizah; Daffa Abrar Musyaffa; Avip Zul’allim; Rizal Fathurrohman (Al-Khazin: Jurnal Pendidikan Agama Islam, 2025)
In the modern era that is increasingly digitally connected, understanding and appreciating nature is a big challenge for future generations. In Islamic teachings, nature is seen as a sign of the greatness of Allah SWT that must be maintained and preserved by humans. Therefore, prospective Islamic Religious Education Teachers have an important role in increasing the love for nature in future generations through PAI learning. By combining Islamic teachings with a creative and inclusive educational approach, PAI teachers can provide a deep learning experience about loving the Nature around us. The research method uses a descriptive qualitative approach with a sample of PAI study program students and students interested in becoming PAI teachers who are selected through purposive sampling techniques. The results of this study speak that the love of nature is taught as part of human responsibility as the caliph of Allah on earth, and education has an important role in building environmental awareness. An effective PAI learning strategy involves combining the concept of Islam with love for the environment, enhancing moral and responsibility learning, personal reflection and sustainable attitude development, and engaging Future Generations with hands-on experience.